Beyond Appendicitis: A Rare Case of Succenturiate Placenta Increta Presenting as Acute Abdomen (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Placenta accreta spectrum (PAS) is a severe obstetric condition characterized by abnormal adherence and invasion of the placenta into the myometrium, often leading to massive hemorrhage and significant maternal morbidity. Despite advances in antenatal imaging, atypical presentations remain diagnostically challenging, particularly in cases with placental morphological variations such as succenturiate lobes. These variants may obscure diagnosis and delay timely intervention.Case Presentation: A 34-year-old multigravida at 32 weeks of gestation presented with acute abdominal pain, initially suggestive of a non-obstetric cause. Initial clinical evaluation and imaging were inconclusive, and the patient was managed conservatively. Due to worsening abdominal pain and rising clinical suspicion, repeat imaging was performed. This revealed a previously undetected succenturiate placental lobe located in the lower uterine segment, showing features consistent with placenta increta, along with hemoperitoneum. The main placental mass was situated anteriorly in the upper uterine segment, contributing to the missed diagnosis in earlier scans.Results: Given the high risk of catastrophic hemorrhage, an emergency cesarean section was undertaken. Intraoperative findings confirmed significant placental invasion with massive hemorrhage, necessitating obstetric hysterectomy and transfusion of blood products. With prompt multidisciplinary management, the patient had an uneventful postoperative recovery.Conclusion: This case highlights the need to consider placenta accreta spectrum in the differential diagnosis of acute abdomen during pregnancy, especially in patients with a history of prior uterine surgery. Thorough placental evaluation, heightened clinical suspicion, and timely multidisciplinary intervention are essential to optimize maternal and fetal outcomes in such rare and life-threatening scenarios.